You Smell Dangerous: Communicating Fight Responses Through Human Chemosignals of Aggression - Mutic, Smiljana; Parma, Valentina; Bruenner, Yvonne F.; Freiherr, Jessica (Chemical Senses, 2016)
The ability to detect conspecifics that represent a potential harm for an individual represents a high survival benefit. Humans communicate socially relevant information using all sensory modalities, including the chemosensory systems. In study 1, we investigated whether the body odor of a stranger with the intention to harm serves as a chemosignal of aggression. Sixteen healthy male participants donated their body odor while engaging in a boxing session characterized by aggression-induction methods (chemosignal of aggression) and while performing an ergometer session (exercise chemosignal). Self-reports on aggression-related physical activity, motivation to harm and angry emotions selectively increased after aggression induction. In study 2, we examined whether receivers smelling such chemosignals experience emotional contagion (e.g., anger) or emotional reciprocity (e.g., anxiety). The aggression and exercise chemosignals were therefore presented to 22 healthy normosmic participants in a double-blind, randomized exposure during which affective/cognitive processing was examined (i.e., emotion recognition task, emotional stroop task). Behavioral results indicate that chemosignals of aggression induce an affective/cognitive modulation compatible with an anxiety reaction in the recipients. These findings are discussed in light of mechanisms of emotional reciprocity as a way to convey not only affective but also motivational information via chemosensory signals in humans.
Keywords: approach motivation; olfaction; social chemosignals; threat